A quality-driven approach for resources planning in Service-Oriented Architectures. Issue 12 (15th July 2015) - Teixeira, Marcelo; Ribeiro, Richardson; Oliveira, Cesar; Massa, Ricardo
Highlights Performance estimation of in-development SOA-based systems. Availability estimation of in-development SOA-based systems. SLA planning for in-development SOA-based systems. Bottleneck discovering and reshaping in SOA processes. Methodology for the incremental improvement of SOA infrastructures.